Interferon-β Induces Cellular Senescence in Cutaneous Human Papilloma Virus-Transformed Human Keratinocytes by Affecting p53 Transactivating Activity - Chiantore, Maria V. (Public Library of Science, 2012)
Interferon (IFN)-β inhibits cell proliferation and affects cell cycle in keratinocytes transformed by both mucosal high risk Human Papilloma Virus (HPV) and cutaneous HPV E6 and E7 proteins. In particular, upon longer IFN-β treatments, cutaneous HPV38 expressing cells undergo senescence. IFN-β appears to induce senescence by upregulating the expression of the tumor suppressor PML, a well known IFN-induced gene. Indeed, experiments in gene silencing via specific siRNAs have shown that PML is essential in the execution of the senescence programme and that both p53 and p21 pathways are involved. IFN-β treatment leads to a modulation of p53 phosphorylation and acetylation status and a reduction in the expression of the p53 dominant negative ΔNp73. These effects allow the recovery of p53 transactivating activity of target genes involved in the control of cell proliferation. Taken together, these studies suggest that signaling through the IFN pathway might play an important role in cellular senescence. This additional understanding of IFN antitumor action and mechanisms influencing tumor responsiveness or resistance appears useful in aiding further promising development of biomolecular strategies in the IFN therapy of cancer.